It’s Not Aid, But Reparations - Milla Vaha (Global justice: Theory, Practice, Rhetoric)
According to Article 8 of the Paris Agreement, parties to the treaty recognise and commit to address, avert and minimise losses and damages associated with adverse effects of climate change. For many societies, such as Small Island Developing States, loss and damage is a matter of survival. Global warming and sea-level-rise are threatening the territories and livelihoods of vulnerable low-lying island states and thereby undermining many of the fundamental human rights and freedoms of individuals living in these societies. This paper looks at loss and damage through the concept of reparations in the context of the coloniality of climate. By studying the case of the Marshall Islands and its history with nuclear testing, the paper argues for a connection between irreversible loss and damage and the right to remedy and reparation by proposing that the nuclear legacy represents a grave violation of the human rights of the Marshallese and has led to a permanent loss of land and other severe impacts on health, culture and livelihoods, which now are exacerbated by climate change.